2021
DOI: 10.1109/tgrs.2020.3041340
|View full text |Cite
|
Sign up to set email alerts
|

Improving ASCAT Soil Moisture Retrievals With an Enhanced Spatially Variable Vegetation Parameterization

Abstract: This study investigates the performance of the TU Wien soil moisture retrieval algorithm (TUW-SMR) by adapting the strength of the vegetation correction. The semiempirical change detection method TUW-SMR exploits the multi-angle backscatter observations from spaceborne fan-beam scatterometer systems in order to derive surface soil moisture information expressed in degree of saturation. The vegetation parameterization of TUW-SMR is controlled by the dry and wet cross-over angles that are used to determine the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…The H SAF ASCAT SSM retrieval scheme is based on the TU Wien change detection model originally developed for the ERS scatterometer [38], and later adapted to ASCAT [2], [39], [40]. This backscatter model is formulated in the decibel domain, assuming that a change in soil moisture leads to a change in backscatter…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The H SAF ASCAT SSM retrieval scheme is based on the TU Wien change detection model originally developed for the ERS scatterometer [38], and later adapted to ASCAT [2], [39], [40]. This backscatter model is formulated in the decibel domain, assuming that a change in soil moisture leads to a change in backscatter…”
Section: Theorymentioning
confidence: 99%
“…To obtain estimates of θ, the model is calibrated for each land surface pixel by extracting minimum and maximum backscatter values from multi-year backscatter time series standardized to a reference angle of 40 • and corrected for seasonal vegetation cover effects [40]- [42]. The so-derived values of σ 0 min and σ 0 max do not only vary from pixel to pixel, but also over the seasons and are assumed to represent completely dry and saturated soil conditions, respectively.…”
Section: Theorymentioning
confidence: 99%
“…The satellite soil moisture data used in this study is the soil water index (SWI) derived from an experimental version of the upcoming disaggregated Metop ASCAT surface Soil Moisture v2 product (H28) provided by the EUMET-SAT Satellite Application Facility on Support to Operational Hydrology and Water Management (H-SAF). The original ASCAT surface soil moisture dataset at 12.5 km (before disaggregation) is based on a new parameterization for the vegetation correction (Hahn et al, 2021), which has shown improved performance over Austria (Pfeil et al, 2018). The disaggregation process consists of a directional resampling method utilizing the connection between regional-(12.5 km) and local-scale (0.5 km) Sentinel-1 backscatter observations describing temporally stable soil moisture patterns also reflected in the radar backscatter measurements (Wagner et al, 2008).…”
Section: Ascat Soil Moisturementioning
confidence: 99%
“…The upper limit ("wet reference") reflects the highest value of backscattering coefficient observed over time at a certain location. They are given by [15]:…”
Section: Tu Wien Soil Moisture Retrievalmentioning
confidence: 99%